Anchorage systems for FRP strengthening of infill masonry structures. (1st January 2013) - Lunn, Dillon S.; Maeda, Shohei; Rizkalla, Sami H.; Ueda, Tamon
An experimental research program consisting of 12 infill wall specimens was undertaken to investigate the effectiveness of several new and existing anchorage systems for fibre-reinforced polymer (FRP) strengthening of infill masonry walls. Specimens were loaded out-of-plane using an airbag to apply uniformly distributed pressure to the masonry. Test results indicate that the anchorage system had a significant effect on the failure mode, ductility, and load carrying capacity of strengthened walls. The increase in strength is between 1.6 and 7.2 times the capacity of the unstrengthened wall. The effectiveness of the anchorage was found to be closely related to its ability to resist shear sliding of the infill panel out of the supporting reinforced concrete frame and the subsequent debonding of the FRP in the anchorage region.